A neutral protease of the neutrophil surface : role in the proteolysis of C-reactive protein and fibrinogen - Kelly, Sharon Lesley (UCT/MRC Liver Research Centre, 2018)
Both of the acute phase reactants, C-reactive protein and fibrinogen, as well as neutrophils have been shown to accumulate at sites of tissue injury or inflammation. The association of C-reactive protein with neutrophils and the concomitant degradation of this ligand by a phorbol 12-myristate 13 acetateactivatable membrane-associated neutral protease has been shown in previous studies. Degradation of C-reactive protein by the neutrophil protease was shown to result in peptides with an ability to modulate various immune functions of the neutrophil. The aim of this study has been to investigate specific characteristics of the protease, with respect to cellular distribution and molecular size. The ability of this neutrophil membrane-associated protease to degrade the acute phase protein, fibrinogen was investigated. The mechanism of degradation of both C-reactive protein and fibrinogen during their association with the neutrophil was also examined. The neutrophil protease, capable of degrading C-reactive protein, was also associated with the cytoskeleton and was proposed to be a submembrane protease localised at sites of attachment of the membrane with the cytoskeleton. The protease was found to have a molecular mass of approximately 600 kDa which, on sodium dodecyl sulphate polyacrylamide gel electrophoresis, separated into four bands which migrated to molecular mass values of 209 kDa, 316 kDa, 398 kDa and 501 kDa. This protease also possessed fibrinogenolytic activity. The fibrinogen degradation products generated by this neutrophil membrane-associated protease were distinct from the products generated by the fibrinogenolytic systems of plasmin, human neutrophil elastase and neutrophil lysosomal enzymes and were unclottable through cleavage of the Aα chain from the N-terminus and the Bβ and γ chains from the C-terminus. N-terminal cleavage of the Aα chain by the neutrophil membrane-associated protease generated the Aα1-21 peptide, previously regarded as a unique consequence of elastase activity. Degradation of C-reactive protein and fibrinogen occurred as a result of their interaction with the neutrophil near to the CD11c integrin receptor. This interaction resulted in the egress of proteolytic activity into the extracellular medium. The fibrinogen products generated outside the cell associated with the neutrophil via the β₂ integrin receptors and the IgG Fc receptor. The interaction of the Creactive protein degradation products with the neutrophil could not be determined. Both C-reactive protein and fibrinogen are degraded by non-stimulated neutrophils but activation with phorbol 12- myristate 13 acetate resulted in maximum degradation This upregulation of activity was achieved through activation of H7 and trifluoperazine inhibitable cellular kinases and changes in microfilament assembly. The generation of non-clottable fibrinogen together with possible modulation of neutrophil receptormediated functions by the fibringen degradation products as well as the knowledge that the neutrophil protease generates C-reactive protein peptides with immunomodulatory activity implicates this neutrophil membrane-associated protease in the modulation of various inflammatory processes.